An Islamic Economic Review of the Determinants of Labor Absorption in Indonesia from 2014 to 2023 - Choirunnisa, Choirunnisa; Fasa, Muhammad Iqbal; Nuraziza, Sania (Jurnal Iqtisaduna, 2025)
This study aims to measure and indentify how the Number of Foreign Tourist 5 ASEAN Countries, namey Brunei, Malaysia, the Philippines, Singapore, and Thailand) and the Number of Hotel Occupancies affect the Number of labor Absorption in the Tourism Sector in Indonesia in 2014-2023. The type of research used in this study uses a quantitative approach with a panel data analysis method. The result of the study indicate that Foreign Tourist Visits have a negative and insignificant effect on Labor Absorption in the Tourism Sector in Indonesia, the Number of Hotel Occupancies has a negative and significant effect on Labor Absorpation in the Tourism Sector in Indonesia. The variables Number of Foreign Tourists and Number of Hotel Occupancies together have a significant effect on Labor Absorption in the Tourism Sector in Indonesia.